If it's not what You are looking for type in the equation solver your own equation and let us solve it.
52x*3+28(3+2x)=58-13x
We simplify the equation to the form, which is simple to understand
52x*3+28(3+2x)=58-13x
Simplifying:
+156x+28*(3+2x)=58-13x
Reorder the terms in parentheses
+156x+(+84+56x)=58-13x
Remove unnecessary parentheses
+156x+84+56x=+58-13x
We move all terms containing x to the left and all other terms to the right.
+156x+56x+13x=+58-84
We simplify left and right side of the equation.
+225x=-26
We divide both sides of the equation by 225 to get x.
x=-0.115555555556
| -33+17=0 | | 3x+33=0 | | 5(t-0.4)+6t=0 | | 1.2c+2.6=4.56 | | (-3x)+17=16 | | -0.5+4+2x=9 | | 5(x-5)+2(14-3x)=7 | | 5(x-5)+2(14-14-3x)=7 | | 1/3(x+2)-x+4/4=3/4 | | -1/2(-x-6)=-x | | 5x+1y+0.25z=100 | | 108-2x=25x+15 | | -7(x-2)=3x-1 | | -15-9x=8x+19 | | 142-4x=5x+16 | | -14-3x=5x+16 | | 12(3-8x)-9(8-9x)=11(12-7x)-8(1-9x) | | 2/3+8*3+x=16 | | 2(3x-6)= | | 25x-5+2x= | | 2a+(3a-7)= | | 25-275x= | | 3x(-2+5)=2 | | 35-5(2z+3)=20 | | x+11=2x+4 | | 4x+1=x+1 | | x+5=2x+1 | | 5x+48=2x+21 | | x^2+4=13 | | 3=3+48t-16t^2 | | Log(2)2=1 | | 4-(x+3)=8-5(2x-3) |